2020
DOI: 10.3390/cells9020328
|View full text |Cite
|
Sign up to set email alerts
|

Poison-Exon Inclusion in DHX9 Reduces Its Expression and Sensitizes Ewing Sarcoma Cells to Chemotherapeutic Treatment

Abstract: Alternative splicing is a combinatorial mechanism by which exons are joined to produce multiple mRNA variants, thus expanding the coding potential and plasticity of eukaryotic genomes. Defects in alternative splicing regulation are associated with several human diseases, including cancer. Ewing sarcoma is an aggressive tumor of bone and soft tissue, mainly affecting adolescents and young adults. DHX9 is a key player in Ewing sarcoma malignancy, and its expression correlates with worse prognosis in patients. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…With regard to the variant we studied and its effects on poison exon inclusion, there is a growing list of therapeutic strategies that target mechanisms related to alternative splicing. An RNA-based therapeutic triggering poison exon inclusion in DHX9 , a gene involved in Ewing sarcoma, has been exploited to enhance the efficacy of chemotherapy in cancer patients [ 41 ]. Additionally, in Duchenne muscular dystrophy and spinal muscular atrophy (SMA), oligonucleotides that promote exon skipping and alternative exon inclusion, respectively, are becoming increasingly applied in clinical settings [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the variant we studied and its effects on poison exon inclusion, there is a growing list of therapeutic strategies that target mechanisms related to alternative splicing. An RNA-based therapeutic triggering poison exon inclusion in DHX9 , a gene involved in Ewing sarcoma, has been exploited to enhance the efficacy of chemotherapy in cancer patients [ 41 ]. Additionally, in Duchenne muscular dystrophy and spinal muscular atrophy (SMA), oligonucleotides that promote exon skipping and alternative exon inclusion, respectively, are becoming increasingly applied in clinical settings [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the intronic variant we studied, there is a growing list of therapeutic strategies that target mechanisms related to alternative splicing. An RNA-based therapeutic triggering poison exon inclusion in DHX9, a gene involved in Ewing sarcoma, has been exploited to enhance the efficacy of chemotherapy in cancer patients [42]. Additionally, targeting RNA splicing of SMN2, haploinsufficiency of which leads to spinal muscular atrophy (SMA), has led to the development of the first FDA-approved drug to treat SMA [43].…”
Section: Discussionmentioning
confidence: 99%
“…A different study revealed that SRSF3 and hnRNPM can bind to DHX9 exon 6A to suppress its inclusion and promote DHX9 expression. Downregulation of these proteins inhibits DHX9 expression, suppresses proliferation and sensitizes Ewing sarcoma cells to doxorubicin treatment, revealing the importance of DHX9 alternative splicing in conferring chemosensitivity or chemoresistance [ 108 ].…”
Section: Dhx9 As a Biomarker And Therapeutic Targetmentioning
confidence: 99%